Imunogenost zaviralcev dejavnika tumorske nekroze alfa - Ogrič, Manca (Farmacevtski vestnik, 2016)
Inflammatory rheumatic diseases represent one of the fastest growing medical fields. The common feature of diseases, included in this group, is an inadequate immune system response to selfantigens. The treatment doctrine in the field of inflammatory rheumatic diseases has completely changed in recent years, mainly due to development of modern biological target drugs. Their main purpose is a targeted inhibition of competent cells and their products - cytokines, which play important roles in the pathogenesis of inflammatory rheumatic diseases. Biological drugs used for inflammatory rheumatic disease treatment are TNF-alpha, IL-1, IL-6, and CD20 + B- cell inhibitors. Among them, TNf-alpha inhibitors are the most frequently used antiinflammatory bio- logical drugs. The two main problems related to their use are primary and secondary treatment failures. A secondary failure is a consequence of the presence of recipients' antibodies developed against biological drugs which cause ineffective treatment and various adverse effects.
Keywords: anti-drug antibodies; biologics; biološka zdravila; immunogenicity; imunogenost; protitelesa proti biološki učinkovini